A scoping Review of Tools to Evaluate Existing Playgrounds for Inclusivity of Children with Disabilities - Taylor, Leah G.; Primucci, Mara; Vanderloo, Leigh M.; Arbour-Nicitopoulos, Kelly P.; Leo, Jennifer; Gilliland, Jason; Tucker, Patricia (Frontiers in Rehabilitation Sciences, 2023)
Children with disabilities may be unable engage playground spaces due to barriers exacerbating exclusion. Therefore, clarity on how to evaluate existing playgrounds for inclusivity of children with disabilities is required. A scoping review was undertaken to explore auditing tools. Fourteen white and grey literature resources were identified. The term ‘inclusion’ was operationalized differently across tools, primarily focusing on physical accessibility. Characteristics of the tools were synthesized into 13 inclusive design recommendations for playgrounds. Two tools showed promise, evaluating 12/13 recommendations. The results of this review provide guidance on existing tools for evaluating playgrounds for inclusion for community stakeholders and researchers.